A two-step indirect inference approach to estimate the long-run risk asset pricing model - Joachim Grammig; Eva-Maria Küchlin (University of Cologne, Centre for Financial Research (CFR), 2017)
The long-run consumption risk model provides a theoretically appealing explanation for prominent asset pricing puzzles, but its intricate structure presents a challenge for econometric analysis. This paper proposes a two-step indirect inference approach that disentangles the estimation of the model's macroeconomic dynamics and the investor's preference parameters. A Monte Carlo study explores the feasibility and efficiency of the estimation strategy. We apply the method to recent U.S. data and provide a critical re-assessment of the long-run risk model's ability to reconcile the real economy and financial markets. This two-step indirect inference approach is potentially useful for the econometric analysis of other prominent consumption-based asset pricing models that are equally difficult to estimate.
Keywords: C58; G10; G12; 330; indirect inference estimation; asset pricing; longrun risk